2019
DOI: 10.1177/0961203319839478
|View full text |Cite
|
Sign up to set email alerts
|

Self-management and adherence in childhood-onset systemic lupus erythematosus: what are we missing?

Abstract: Objectives The aims of this study are (1) to characterize factors influencing self-management behaviors and quality of life in adolescent and young adult (AYA) patients with childhood-onset systemic lupus erythematosus (cSLE) and (2) to identify barriers and facilitators of treatment adherence via focus groups. Methods AYAs with cSLE ages 12–24 years and primary caregivers of the adolescents participated in this study. Recruitment occurred during pediatric rheumatology clinic visits at a Midwestern children's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…cSLE patients are mainly in the adolescence period [ 20 ]. This transitional phase to adulthood involves several physical and emotional changes [ 37 ], and the impact of this complex disease may affect their self-management and self-esteem [ 174 , 175 ]. In fact, a cSLE study in adolescents and young adults with a semi-structured interview showed that the use of medication served as reminders of their illness and made them feel abnormal [ 176 ].…”
Section: Drug Adherence For Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…cSLE patients are mainly in the adolescence period [ 20 ]. This transitional phase to adulthood involves several physical and emotional changes [ 37 ], and the impact of this complex disease may affect their self-management and self-esteem [ 174 , 175 ]. In fact, a cSLE study in adolescents and young adults with a semi-structured interview showed that the use of medication served as reminders of their illness and made them feel abnormal [ 176 ].…”
Section: Drug Adherence For Adolescentsmentioning
confidence: 99%
“…Thus, it is recommended that medication adherence should be checked during the pediatric rheumatologist appointments, especially before any decisions around treatment modifications [ 2 , 96 ]. Understanding and responding to adolescent demands with a personalized treatment plan and multidisciplinary teams, including psychological/psychiatric support, health education strategies, and adherence interventions may help cSLE teens to increase compliance with treatment [ 37 , 174 , 176 , 181 , 182 ].…”
Section: Drug Adherence For Adolescentsmentioning
confidence: 99%
“…Characteristics unique to cSLE make adherence particularly difficult, including number of medications, the complexity of medication regimens, medication-related organ damage, disease flares, and psychological manifestations [7,8]. For young adults with rheumatic diseases, adherence barriers include forgetfulness, polypharmacy, cost, personal problems, and/or refusal [9,10]. Specific to those with cSLE, medication-specific knowledge deficits and the lack of perceived improvement in daily symptoms are significant barriers to medication adherence [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For young adults with rheumatic diseases, adherence barriers include forgetfulness, polypharmacy, cost, personal problems, and/or refusal [9,10]. Specific to those with cSLE, medication-specific knowledge deficits and the lack of perceived improvement in daily symptoms are significant barriers to medication adherence [2,10,11]. In addition, real or perceived side effects, low medication literacy, and/or poor medication taste were identified as adherence barriers in cSLE.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized trial assessing the feasibility and acceptability of automated digital reminders and a personalized prescribed treatment plan in young adults with cSLE assessed baseline pain intensity and fatigue using the PROMIS‐SFs for pain intensity and fatigue (63). The fatigue PROMIS‐SF was also an outcome measure in an observational study assessing self‐management and adherence in adolescents and young adults with cSLE (64).…”
Section: Promis Short Formsmentioning
confidence: 99%